Study on microstructure and mechanical properties of steel corrosion products in marine environment - Tang, Bowen; Wang, Wei; Yang, Haicheng; Zhu, Haiwei (Frontiers in Materials, 2024)
The microstructure and mechanical properties of steel corrosion products in marine environment are key parameters for developing the concrete corrosion-induced model. In this study, steel corrosion products from steel plates, concrete specimens with 10 mm and 20 mm covers, and cracked beams in Zhejiang province were sampled and analyzed. Initially, the microstructure of the steel corrosion products were determined by X-ray diffractometry (XRD), thermogravimetric analysis (TG), scanning electron microscopy (SEM), and energy-dispersive spectrometry (EDS).Subsequently, the mechanical properties of steel corrosion products including nanoindentation elastic modulus, hardness and instantaneous elastic modulus were measured by nanoindentation and consolidation experiments. This study holds potential for establishing the concrete corrosioninduced model and assessment of the concrete structure durability in marine environment.